2019
DOI: 10.1101/578468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reward boosts neural coding of task rules to optimise cognitive flexibility

Abstract: Cognitive flexibility is critical for intelligent behaviour. However, its execution is effortful and often suboptimal. Recent work indicates that flexible behaviour can be improved by the prospect of reward, suggesting that rewards optimise flexible control processes. Here we investigated how different reward prospects influence neural encoding of task rule information to optimise cognitive flexibility. We applied representational similarity analysis (RSA) to human electroencephalograms, recorded while partici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Plenty of studies have shown that higher performance-contingent incentives can facilitate a set of high-order cognitive/adaptive control processes, including inhibitory control (Diao et al, 2016; Herrera et al, 2014; Zhang et al, 2016), task-switching (Etzel et al, 2015; Hall-McMaster et al, 2019; Wisniewski et al, 2015), conflict control (Krebs et al, 2010; Padmala & Pessoa, 2011), and adaptation to conflict control (Braem et al, 2012, 2014). While reward is generally associated with performance enhancement, the presence of conflicting information is widely known to impede human behavior, as illustrated by conflict tasks such as flanker, Stroop, and Simon tasks (Eriksen & Eriksen, 1974; Simon & Rudell, 1967; Stroop, 1935).…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of studies have shown that higher performance-contingent incentives can facilitate a set of high-order cognitive/adaptive control processes, including inhibitory control (Diao et al, 2016; Herrera et al, 2014; Zhang et al, 2016), task-switching (Etzel et al, 2015; Hall-McMaster et al, 2019; Wisniewski et al, 2015), conflict control (Krebs et al, 2010; Padmala & Pessoa, 2011), and adaptation to conflict control (Braem et al, 2012, 2014). While reward is generally associated with performance enhancement, the presence of conflicting information is widely known to impede human behavior, as illustrated by conflict tasks such as flanker, Stroop, and Simon tasks (Eriksen & Eriksen, 1974; Simon & Rudell, 1967; Stroop, 1935).…”
Section: Introductionmentioning
confidence: 99%